1983
DOI: 10.3109/10641968309081788
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Metabolic Effects of ACTH in Normotensive and Hypertensive Man

Abstract: ACTH administration (0.5 mg Synacthen Depot I/M 12 hourly for 5 days) significantly increased systolic blood pressure in normotensive subjects (n=6) and mild essential hypertensives (n=6) but not in 2 Addisonian women, indicating that the pressure rise was adrenally dependent. ACTH administration was associated with urinary sodium retention, hypokalaemia, elevation of fasting blood glucose, lymphopaenia and eosinopaenia. Body weight was increased only in the normotensive subjects. Plasma renin concentration fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…In fact, (i) hypophysectomy induces adrenal atrophy of the cortex and not of the adrenal medulla (Swann, 1940), (ii) cerebrospinal fluid (CSF) and plasma concentration of ACTH are correlated (Banks and Kastin, 1995) and sustained during ageing and (iii) compensatory factors in HPA regulation do exist (Lamberts et al, 1997). In addition, ACTH (i) increases mRNA of mitochondrial encoded genes involved in oxidative phosphorylation (Das, 2006), (ii) via glucocorticoids, it is an inducer of transaminases (Turchetto and Cenciotti, 1957) and (iii) ACTH is partially involved in mineralcorticoids release (Whithworth et al, 1983;Biglieri et al, 1987), whose effects in nervous tissue are mediated by Na + , K + -ATP-ase. This enzyme activity diminished in late ageing CTX (Benzi et al, 1993(Benzi et al, , 1994, together with that of other ATP-ases, suggesting that some HPA impairments may take place also at late age.…”
Section: Effect Of Ageing On the Frontal Cerebral Cortex Energy Metabmentioning
confidence: 98%
“…In fact, (i) hypophysectomy induces adrenal atrophy of the cortex and not of the adrenal medulla (Swann, 1940), (ii) cerebrospinal fluid (CSF) and plasma concentration of ACTH are correlated (Banks and Kastin, 1995) and sustained during ageing and (iii) compensatory factors in HPA regulation do exist (Lamberts et al, 1997). In addition, ACTH (i) increases mRNA of mitochondrial encoded genes involved in oxidative phosphorylation (Das, 2006), (ii) via glucocorticoids, it is an inducer of transaminases (Turchetto and Cenciotti, 1957) and (iii) ACTH is partially involved in mineralcorticoids release (Whithworth et al, 1983;Biglieri et al, 1987), whose effects in nervous tissue are mediated by Na + , K + -ATP-ase. This enzyme activity diminished in late ageing CTX (Benzi et al, 1993(Benzi et al, , 1994, together with that of other ATP-ases, suggesting that some HPA impairments may take place also at late age.…”
Section: Effect Of Ageing On the Frontal Cerebral Cortex Energy Metabmentioning
confidence: 98%
“…Exogenous ACTH (1 mg/d) administered to normotensive subjects can also raise their blood pressures by Ϸ20 mm Hg over the treatment period. 4 When ACTH is given by constant intravenous infusion, rates as low as 50 g/d raise pressure. ACTH concentrations rose with the infusion but remained within the normal range, suggesting that concentrations achieved under physiological conditions could be sufficient to raise blood pressure in humans.…”
Section: Discussionmentioning
confidence: 99%
“…1 This receptor is expressed in the adrenal cortex but has been recently identified in extra-adrenal tissues such as human skin 2 and mouse adipose tissue. 3 Previous studies showed that the administration of ACTH (1-24) caused an increase in blood pressure in normotensive and hypertensive subjects, whereas no change was observed in patients with adrenal insufficiency, 4 and the effect of ACTH (1-24) was mimicked by cortisol. 5 Thus, the rise in pressure has been believed to be due to ACTH-induced increases in cortisol secretion in the adrenal gland.…”
mentioning
confidence: 99%
“…Adrenocorticotrophic hormone (ACTH) administration increases blood pressure in rats (1) and humans (2). Although it has been thought that ACTH-induced hypertension is due to glucocorticoid activation of mineralocorticoid receptors with consequent salt and water retention, such hypertension is not prevented by mineralocorticoid receptor blockade (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%